Shari'ah Compliant Matrix for Humanizing Productivity - Category 4: Physical Workplace - Mahamod, Lukman Hakim (2021)
The physical environment at work plays a vital role in employees' productivity; therefore, this matrix covers nine 9 categories of physical facilities required for humanizing productivity, preservation of Islamic religion and values in higher Islamic education.